Education and public outreach in astronomy and beyond. (January 2018) - Cominsky, Lynn
Education and public outreach has evolved from being part of a scientist's duties into a distinct career path that is well-suited for astronomers. The ideal professional in this field has strong communication skills coupled with a broad research background.